EDUCATION FOR ALL AND MULTIGRADE TEACHING - LITTLE, ANGELA W.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Multigrade teaching poses a challenge to learning. Millions of learners worldwide are taught by teachers who, at any one time, are responsible for two or more school grades/years. These are the invisible multigrade teachers who struggle to provide learning opportunities for all within curriculum and teacher education systems designed for monograded classes. In many countries multigraded classes arise out of necessity and are regarded as second class education. Yet in some parts of the world learning and teaching in multigraded settings is embraced as the pedagogy of choice, offering equivalent, and sometime superior, learning opportunities. Multigrade teaching provides an opportunity for improved learning. This book is based on original research on challenges and opportunities in Colombia, England, Ghana, Malawi, Nepal, Sri Lanka, Sudan, Peru, Turks and Caicos and Vietnam. Its purpose is to raise awareness among educational policymakers and practitioners worldwide of the realities of multigrade classes in the context of Education for All, and to explore the implications for teachers, teacher educators, curriculum developers and educational planners.
Education for all: multigrade realities and histories -- Learning opportunities for all: pedagogy in multigrade and monograde classrooms in the Turks and Caicos Islands -- A multigrade approach to literacy in the Amazon, Peru: school and community perspectives -- Multigrade teaching in London,England -- Multigrade teachers and their training in rural Nepal -- Prepared for diversity? Teacher education for lower primary classes in Malawi -- Adapting the primary mathematics curriculum to the multigrade classroom in rural Sri Lanka -- Improving the quality of health education in multigrade schools in Vietnam -- Adapting the curriculum for teaching health in multigrade classes in Vietnam -- EFA for pastoralists in North Sudan: a mobile multigrade model of schooling -- Extending basic education to out-of-school children in Northern Ghana: what can multigrade schooling -- Costs and finance of multigrade strategies for learning: how do the books balance -- Escuela nueva's impact on the peaceful social interaction of children in Colombia -- Multigrade lessons for EFA: a synthesis.
Keywords: EDUCATION; CURRICULUM PLANNING; EDUCATION; EDUCATIONAL POLICY AND POLITICS; INTERNATIONAL AND COMPARATIVE EDUCATION; CURRICULUM STUDIES; LEARNING & INSTRUCTION; TEACHING AND TEACHER EDUCATION